2017
DOI: 10.31234/osf.io/jfgvq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Depressed adolescents' pupillary response to peer acceptance and rejection: The role of rumination

Abstract: Heightened emotional reactivity to peer feedback is predictive of adolescents’ depression risk.Examining variation in emotional reactivity within currently depressed adolescents’ may identifysubgroups that struggle the most with these daily interactions. We tested whether traitrumination, which amplifies emotional reactions, explained variance in depressed adolescents’physiological reactivity to peer feedback, hypothesizing that rumination would be associatedwith greater pupillary response to peer rejection an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…the loss of a romantic relationship has been found to trigger a first episode of depression [92,93]. Recent work has investigated ecological measures of social reward such as social acceptance and rejection from peers and finds that in adolescents with depression both increased reactivity to negative and blunted reactivity to positive social feedback [94][95][96]. Furthermore when investigating social status descriptors the same research group recently found hypoactivation in the superior temporal cortex and medial prefrontal cortex, and reduced late activation in the dorsolateral prefrontal cortex and fusiform gyrus to negative (vs. positive) social status words in depressed youth compared to controls.…”
Section: Anhedonia and Reward Processing In Adolescent Mdd-neural Stumentioning
confidence: 99%
“…the loss of a romantic relationship has been found to trigger a first episode of depression [92,93]. Recent work has investigated ecological measures of social reward such as social acceptance and rejection from peers and finds that in adolescents with depression both increased reactivity to negative and blunted reactivity to positive social feedback [94][95][96]. Furthermore when investigating social status descriptors the same research group recently found hypoactivation in the superior temporal cortex and medial prefrontal cortex, and reduced late activation in the dorsolateral prefrontal cortex and fusiform gyrus to negative (vs. positive) social status words in depressed youth compared to controls.…”
Section: Anhedonia and Reward Processing In Adolescent Mdd-neural Stumentioning
confidence: 99%
“…One factor accounting for significant heterogeneity in the effects of peer stressors on adolescent physical health is mental health, such that adolescents with preexisting psychological vulnerabilities show amplified reactivity to interpersonal problems. For example, adolescents with more anxiety and depressive symptoms show stronger psychophysiological responses to social-evaluative stress (e.g., peer rejection; Stone et al, 2016;Tan et al, 2012), suggesting that poor mental health can exacerbate the "sting" of negative peer encounters (Zimmer-Gembeck, 2016). Whether similar patterns account for individual differences in pathways from peer problems to asthma symptoms via impaired sleep, however, is unknown.…”
mentioning
confidence: 99%
“…We opted for such a procedure because it is suitable for "exploratory studies of focally and/or broadly distributed effects" in which it is critical not to have Type II errors (Groppe et al, 2011a, Table 2). This method has already been used in the analyses of PD when it was deemed important to explore time-dependent PD modulations as a function of experimental manipulations while statistically controlling for the proportion of false positives (e.g., Stone et al, 2015). Since, for the present study, it was particularly relevant to investigate pupillary responses as an index of sustained emotional/cognitive processing, analysis of PD peaks or averages would not have been suitable.…”
mentioning
confidence: 99%